An outline of the actions of the communist security apparatus against the Ukrainian population in Ziemia Lubuska in 1947-1989 = Zarys działań komunistycznego aparatu bezpieczeństwa wobec ludności ukraińskiej na Ziemi Lubuskiej w latach 1947-1989 - Słabig, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Settled after the "Vistula" Operation in Ziemia Lubuska, the Ukrainian population was supervised by the communist security apparatus. All displaced people were subjected to surveillance, irrespective of the degree of loyalty to the new authority. Operational work on Ukrainians was conducted with varying intensity throughout all the period of the People`s Republic of Poland.
Keywords: ziemia lubuska; communist security apparatus; Ukrainian people; komunistyczny aparat bezpieczeństwa; ludność ukraińska